Effect Of Tillage Method, Crop Residue And Nutrient Management On Growth And Yield Of Wheat In Rice-Wheat Cropping System At Bhairahawa Condition (Agronomy Journal of Nepal, 2021)
Wheat (Triticum aestivum L), grown under traditional practices becoming less productive and less profitable in Nepal, due to ever-increasing input prices and intensive land preparation. A field experiment was conducted to find alternate practices for enhancing productivity of wheat at the National Wheat Research Program, Bhairahawa during the winter season of 2018/19 and 2019/20. The experiment plot was designed on strip-split plot design with 3 replications. Three tillage methods, surface seeding (SS), zero tillage (ZT), and conventional tillage (CT) were assigned in vertical strips with two levels of crop residue management: residue removed (R0) and residue retention (R50) in horizontal blocks, whereas three levels of nutrient management: recommended dose of NPK (F100), 25% higher dose of NPK (F125) and farmer’s practice (FP) were assigned in subplots. Data regarding growth, yield attributes, and yield were recorded and analyzed by Genstat. In the first year, ZT was better in terms of number of tillers at maximum tillering stage, maximum leaf area index, effective tiller per square meter, number of grain per spike, and straw yield compared to SS and CT; whereas in the second year SS was better in terms of growth, yield attributes and yield as compared to ZT and CT. In the first year, R(0) produced significantly higher straw yield but significantly lower harvest index (HI) than R(50) whereas in second year R(50) produced significantly higher thousand grain weight, grain yield and HI. The application of 25% more nutrients than the recommended dose resulted significantly better most of the growth, yield attributes, and yield during both years. On the average of two years, ZT produced more yield than CT and SS by 26.6% and 3.0% respectively. The short term ZT significantly increased the bulk density as compared to SS and CT. Based on the research results, it can be suggested that the traditional practices of wheat can be replaced by ZT with retention of previous crop residues and the application of 25% more nutrients than the recommended dose.